2022
DOI: 10.3389/fpsyg.2022.986217
|View full text |Cite
|
Sign up to set email alerts
|

Bodies out of control: Relapse and worsening of eating disorders in pregnancy

Abstract: BackgroundBeing pregnant is a vulnerable period for women with a history of eating disorders. A central issue in eating disorders is searching control of one’s body and food preferences. Pregnancy implies being increasingly out of control of this. Treatment and targeted prevention start with the patient’s experience. Little is known about how women with a history of eating disorder experience being pregnant.MethodWe interviewed 24 women with a history of eating disorder at the time of pregnancy, recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This unified and unambiguous pattern of core phenomena among women with a history of AN undergoing IVF contrasts with our previous study. In that study, we found that women with a history of severe eating disorders in general, attributed a very different psychological meaning to being pregnant ( Sommerfeldt et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This unified and unambiguous pattern of core phenomena among women with a history of AN undergoing IVF contrasts with our previous study. In that study, we found that women with a history of severe eating disorders in general, attributed a very different psychological meaning to being pregnant ( Sommerfeldt et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have indicated that women with a history of eating disorders are particularly at risk of deteriorating mental health during pregnancy and early motherhood, including relapse or worsening of their eating problems ( Arnhold et al, 2019 ; Sollid et al, 2021 ; Sommerfeldt et al, 2022 ). Furthermore, infertility, IVF, and its side effects seem to increase the risk of worsening or relapse of eating disorders ( Suthersan et al, 2011 ; Grilo et al, 2012 ; Bruneau et al, 2017 ; Janas-Kozik et al, 2021 ), or of promoting disordered eating ( Hecht et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy and early motherhood are known to be vulnerable times for women with EDs (3)(4)(5)(6)(7). Reported prevalence during pregnancy is 5-8% (8,9), increasing to 12.8% after birth (9), compared with 0.8% for AN and 2.8% for BN for comparable age groups in the general population (10).…”
Section: Introductionmentioning
confidence: 99%